2022
DOI: 10.3389/frai.2022.903051
|View full text |Cite
|
Sign up to set email alerts
|

The potential of learning with (and not from) artificial intelligence in education

Abstract: AI-powered technologies are increasingly being developed for educational purposes to contribute to students' academic performance and overall better learning outcomes. This exploratory review uses the PRISMA approach to describe how the effectiveness of AI-driven technologies is being measured, as well as the roles attributed to teachers, and the theoretical and practical contributions derived from the interventions. Findings from 48 articles highlighted that learning outcomes were more aligned with the optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…AI in Education: Current Applications Implementing AI technology in education could transform the educational experience for overseas students [22]. The usefulness of this technology has grown quickly in recent years, spurring an enormous increase in research on AI and education [23]. AI-powered solutions that provide teachers with insights into how students respond to learning content and style can assist create a more dedicated learning environment for students from different backgrounds [24].…”
Section: 1mentioning
confidence: 99%
“…AI in Education: Current Applications Implementing AI technology in education could transform the educational experience for overseas students [22]. The usefulness of this technology has grown quickly in recent years, spurring an enormous increase in research on AI and education [23]. AI-powered solutions that provide teachers with insights into how students respond to learning content and style can assist create a more dedicated learning environment for students from different backgrounds [24].…”
Section: 1mentioning
confidence: 99%
“…The scientific sources demonstrate that the trends in the studying AI in education focus mainly on enhancing learning experiences (Chichekian & Benteux, 2022), improving educational outcomes (Demartini et al, 2024), and addressing challenges in the implementation of AI technologies (Kamalov et al, 2023). It was found that recent articles are dedicated to one of the following topics: personalized learning (Demartini et al, 2024), intelligent tutoring (Lai et al, 2023), data analytics and predictive modelling (Gómez-Pulido et al, 2023).…”
Section: Current Trends Of the Studying Ai In Educationmentioning
confidence: 99%
“…All this indicates that AI has the considerable potentials to transform modern education through personalized learning, automated processes, intelligent tutoring, and interactive content (Chichekian & Benteux, 2022;Kamalov et al, 2023). At the same time, efficient use of AI-based technologies at the institutions of higher education requires detailed analysis of AI ethics in education (Choi et al, 2024) and development of specific skills necessary for work with AI tools (Rios-Campos et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating AI applications in education has the potential to revolutionize the learning experience for international students, as emphasized by Seldon and Abidoye [17]. There has been a significant increase in research on AI and education in recent years [18], as the practicality of this technology has rapidly evolved [19]. AI-powered tools can provide instructors with insights into how students respond to learning content and style, creating a more dedicated learning atmosphere for international students from diverse backgrounds.…”
Section: Current Applications Of Ai In Educationmentioning
confidence: 99%